1930
DOI: 10.1002/hlca.19300130302
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der Cellulose‐xanthogenate. I. Mitteilung

Abstract: 11. no.Trotzdern die Kunstseidenindixstri~~ jiihrlich ca. 150000 Toiinen Kunstseide nach dem Viskoseverfahren herstellt, ist es his heute iioch nicht gelungen, die beim Sulfidierungsprozess sich ahspielenden Vorgiinge restlos aiifzukliiren. WBhrend man sieh i'ruher noch daruber stritt, ob die Sulfidierung ein rein kolloidchemischer oder ein rein chemiseher Vorgang ist, so hat man sich heute der letzteren Auffassung angeschlossen. Urn die chemische Reaktion restlos erfasscn zu kiinnen, rniissen noch eine Reihe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1930
1930
1957
1957

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The literature failed to disclose a quantitative method for the determination of either mono-or dinitrothiophene. Meyer and Stadler found that dinitrothiophene gives a violet color with alcohol containing a trace of sodium hydroxide (3). A method based on this color reaction had been used for some time in these laboratories for the detection of dinitrothiophene in nitrobenzene.…”
Section: Determination Of Mononitrothiophene and Dinitrothiophene In ...mentioning
confidence: 99%
“…The literature failed to disclose a quantitative method for the determination of either mono-or dinitrothiophene. Meyer and Stadler found that dinitrothiophene gives a violet color with alcohol containing a trace of sodium hydroxide (3). A method based on this color reaction had been used for some time in these laboratories for the detection of dinitrothiophene in nitrobenzene.…”
Section: Determination Of Mononitrothiophene and Dinitrothiophene In ...mentioning
confidence: 99%
“…Schließlich konnte noch Lang(21) zeigen, daß keine der formulierten Reaktionen -wie zu erwarten -vollständig (im Sinne von links nach rechts) abläuft.Fine Sucilfiö^c bUdct auch die Frage nach der Existenz von freiem Na 2 S im Reaktion>gcnv ,ch. Wäh-rend Geiger, Kita u. a (22). die Existcnx von freiem Na.^S -speziell in Viskose -in Abrede stellen, deuten vor allem die verschiedenen potcniiometrischcn Untersuchungen auf die Anwesenheit von Sulfid hin, welche*· sich im Anfang der Reaktion langsam bildet, um nach Durchschreiten eines Maximums gegen Rcaktionsende wieder zu verschwinden (Abb.…”
unclassified
“…Further, from the decrease in total sulfur it is clear that some volatile sulfur compound must have been formed and subsequently lost to the atmosphere. As a first assumption it seems reasonable to suppose that this volatile substance is carbon disulfide, particularly since it is known that, when carbon disulfide is added to viscose, a further xanthation of the cellulose xanthate is readily effected (3,9,10,12).…”
mentioning
confidence: 99%